INDICATORS AND METHODS FOR ASSESSING INTERBANK COMPETITION ENVIRONMENT: THE CASE OF UZBEKISTAN BANKING SECTOR - Madina Ataboyevna Ataboyeva (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2026)
This article provides comprehensive analysis of indicators and methods for assessing the interbank competition environment in Uzbekistan's banking sector based on empirical data from 2020-2024.